THE INFLUENCE OF MACROECONOMIC VARIABLES ON THE STOCK MARKET IN THE UNITED STATES OF AMERICA - Josip Visković; Marko Miletić; Karlo Grbac (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The stock market is an important indicator of the growth and development of a country and its economy, especially the U.S. as a market-based financial system. The added importance of this capital market lies in the importance of the U.S. economy to the world, and, therefore, it is essential to understand the determinants of changes in the U.S. stock market in order to understand expectations for future economic development. This paper, therefore, examines the impact of macroeconomic variables on the U.S. stock market. The study uses the augmented Dickey-Fuller test (ADF test), the Johansen cointegration test, and the Vector Error Correction Model (VECM). Monthly data from January 1995 to December 2019 were used. The study found a statistically significant positive impact of the index of industrial production, money aggregate M1, and long-term interest rates on the value of the S&P 500 index, and a statistically significant negative impact of the consumer price index. The impact of the short-term interest rate was not statistically significant.